Cahokia: Urbanization, Metabolism, and Collapse - Tainter, Joseph A. (Frontiers in Sustainable Cities, 2019)
Cahokia in the twelfth century A.D. was the largest metropolitan area and the most complex political system in North America north of Mexico. Its metabolism depended on an area of high natural and agricultural productivity. As it grew, Cahokia absorbed much of the rural population, transforming their labor from agriculture to public works. As Cahokia collapsed, this population first reoccupied the countryside, then left the region. Cahokia's sustaining area was largely abandoned until the nineteenth century. Factors pertinent to understanding the collapse of Cahokia include societal metabolism, complexity, level of public works, the status of the support population, and growth within the elite stratum.